Effect of pore structure on the piezoelectric properties of barium titanate-polyvinylidene fluoride composite films. (May 2023) - Kowalchik, Tim; Khan, Fariha; Le, Katrina; Leland, Paige; Roundy, Shad; Warren, Roseanne
Abstract: Piezoelectric voltage generation in porous barium titanate-poly(vinylidene fluoride) (BT-PVDF) particle-matrix composite films is investigated as a function of PVDF pore structure and porosity. BT-PVDF composite films fabricated via coagulation bath method attain distinct pore structures depending on the ethanol content of the bath. With increasing bath ethanol content, film morphology shifts from higher porosity finger-like cavities to lower porosity mesh-like structures. Finger-like films have a lower Young's modulus than mesh-like films (224 MPa vs. 368 MPa), but produce higher piezoelectric output voltage when compressed compared to mesh-like films (400 mV vs. 57 mV under 3 N compression). The difference in piezoelectric response is attributed to differences in stress transfer between polymer matrix and ceramic particles. Finite element simulations reveal that finger-like structures produce well-ordered compressive stress while mesh-like structures produce poor stress alignment. The results indicate that improved stress transfer between polymer matrix and ceramic particles can be achieved with well-aligned pore structures, leading to higher piezoelectric output. Graphical Abstract: ga1 Highlights: Pore shape in PVDF-BT a larger driver of piezoelectricity than mechanical properties. Finger-like pores stress BT more effectively than random mesh-like pores. Finger-like pores show 7x the piezoelectric output than mesh-like.